Relationship Between Diet and Physical Activity with the Event of Anemia in Pregnant Women - Dewi, Sri Sartika Sari; Hasibuan, Darma Afni; Aswan, Yulinda; Harahap, Meilani; Anggraini, Wiwik (International Journal of Public Health Excellence (IJPHE), 2022)
The prevalence of anemia in pregnant women is 41.8 % . The causes of anemia in pregnancy include gravida, age, parity, education level, economic status and compliance with Fe tablet consumption, diet and physical activity. The purpose of this study was to determine the relationship between diet and physical activity with the incidence of anemia in pregnant women at Batunadua Health Center, Padangsidimpuan City in 2021 . The type of research is quantitative research with a cross sectional approach study . The population in this study were all pregnant women at Batunadua Health Center Padangsidimpuan City as many as 229 people. The sample in this study were 70 pregnant women at Batunadua Public Health Center, Padangsidimpuan City using random sampling method . The analysis used is Chi Square and Kolmogorov-Smirnov test . The results of this study indicate that there is a relationship between diet ( p=0.000) , and physical activity ( p=0.000) with the incidence of anemia in pregnant women. The conclusion is that diet and physical activity have a relationship with the incidence of anemia in pregnant women. Suggestions for pregnant women to increase antenatal care visits and find out about the incidence of anemia in pregnancy.